Development and evaluation of microporous osmotic tablets of diltiazem hydrochloride - Afifa Bathool; D V Gowda; Mohammed S Khan; Ayaz Ahmed; S L Vasudha; K Rohitash (Journal of Advanced Pharmaceutical Technology & Research, 2012)
Microporous osmotic tablet of diltiazem hydrochloride was developed for colon targeting. These prepared microporous osmotic pump tablet did not require laser drilling to deliver the drug to the specific site of action. The tablets were prepared by wet granulation method. The prepared tablets were coated with microporous semipermeable membrane and enteric polymer using conventional pan coating process. The incorporation of sodium lauryl sulfate (SLS), a leachable pore-forming agent, could form in situ delivery pores while coming in contact with gastrointestinal medium. The effect of formulation variables was studied by changing the amounts of sodium alginate and NaCMC in the tablet core, osmogen, and that of pore-forming agent (SLS) used in the semipermeable coating. As the amount of hydrophilic polymers increased, drug release rate prolonged. It was found that drug release was increased as the concentration of osmogen and pore-former was increased. Fourier transform infrared spectroscopy and Differential scanning calorimetry results showed that there was no interaction between drug and polymers. Scanning electron microscopic studies showed the formation of pores after predetermined time of coming in contact with dissolution medium. The formation of pores was dependent on the amount of pore former used in the semipermeable membrane. in vitro results showed acid-resistant, timed release at an almost zero order up to 24 hours. The developed osmotic tablets could be effectively used for prolonged delivery of Diltiazem HCl.